Strategi Public Relations Dalam Mempertahankan Citra Perusahaan : Studi Pada Program Pelayanan Prima PT. Tiki Jalur Nugraha Ekakurir Pada Masa Covid-19 - Asfian Muhammad Asfian Eko (Prisani Cendekia Institute, 2022)
This study aims to find out what strategy the PR of PT. JNE in maintaining the company's image through excellent service and knowing how the PR strategy process of PT. JNE in maintaining the company's image through excellent service by using service theory and management strategy. The method used is descriptive qualitative using primary and secondary data sources. Data retrieval technique is done by. Researchers used four stages, namely data collection, data reduction, data presentation, and data triangulation. The final result of the research shows the strategies and processes carried out by PT. Tiki Lintas Nugraha Ekakurir is a public relations strategy with a social responsibility approach. Through the excellent service program activities, namely collaborating in helping the delivery of health personal protective equipment, donating money to the government, spraying disinfectants and distributing masks in the community. From this strategic process, a responsible approach is taken to achieve positive results for the company's image. As well as the activities carried out by PT. Tiki JNE during the covid-19 period in Indonesia, got a positive corporate image from JNE users who collaborated to send donations and recipients of assistance carried out by JNE.